Working Parents and Child Care: Charting a New Course for Quality - Lahti, Michael; Connelly, Rachel; Nigro, Georgia; Fraser-Thill, Rebecca (Maine Policy Review, 2009)
Close to two-thirds of children in Maine under the age of five need child care while their parents work. The quality of child care is a critical policy concern, since research has found that early childhood experience plays a major role in later-life success for individuals. The authors report on findings from three studies regarding child care arrangements in Maine and the quality of child care in the state and nationally. They describe the development and implementation of Maine’s new Quality Rating System (QRS) for child care facilities, Quality for ME, and the role that it can play both in improving child care and in helping parents chose quality care.
Keywords: Maine; child care; child care quality rating